Analisis Pengaruh Beban Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di Shopee Express Cabang Lamongan - Aprilyanto, Mochamad David; Pratama, M. Adhitya Nugraha (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The study examined how workload and work motivation influence the performance of employees at Shopee Express Lamongan Branch, focusing on 52 employees. Data was gathered through questionnaires and analyzed using a multiple linear regression model. The findings indicated that both workload and work motivation independently have a partial effect on employee performance. This means that when considering each factor individually, both workload and work motivation can influence performance outcomes in different ways. The null hypothesis was rejected, implying that there is a significant relationship between the variables and employee performance. The results suggest that workload, which can either increase or reduce performance depending on its intensity, and work motivation, which drives employees to perform better, are crucial factors in shaping overall job performance. These findings have important implications for management, as they highlight the need for balancing workload and fostering high motivation to optimize employee performance. By addressing these two aspects, companies can create a more efficient and motivated workforce, leading to better productivity and job satisfaction.